Common forms of strabismus in a tertiary eye clinic in Southwest Nigeria (2019)
Background: Strabismus occurs worldwide and is associated with undesirable psychosocial impact and negative social prejudice. However, there is a dearth of information on the different subtypes of strabismus in Nigerian patients. The aim of this study is to describe the common forms of strabismus among patients of an eye clinic in southwestern Nigeria. Methods: We retrospectively reviewed all new patients seen at the eye clinic of our hospital between January 1999 and December 2008. Patients with a diagnosis of strabismus were identified from the clinic registers and their case records were reviewed. Information on age, gender, cause, and type of squint as well as associated ocular/systemic disease was retrieved from the case records. Results: A total of 240 patients had strabismus, giving a relative frequency of 1.2%. Mean age of patients with strabismus was 19.8 (±19.7) years while male-to-female ratio was 0.98:1. Esotropia (53.8%) was more common than exotropia (44.2%). The mean age of patients with esotropia was 12.8 years compared with 27.9 years for patients with exotropia (P < 0.001). Sensory strabismus was the most common form of strabismus, occurring in 83 (34.5%) patients, while accommodative esotropia was found in only 5.8% patients. Conclusion: The relative frequency of strabismus in this study is fairly similar to other reports from Nigeria and Africa. Secondary strabismus was quite common whereas primary forms of strabismus such as accommodative esotropia appear to occur less frequently among our patients in comparison to Caucasian populations.